2018
DOI: 10.1177/1367006918786467
|View full text |Cite
|
Sign up to set email alerts
|

Structure complexity effects in child heritage Spanish: The case of the Spanish personala

Abstract: Aims and objectives: This study examines the acquisition of Differential Object Marking (DOM) in heritage Spanish children born in the USA and the potential role of structure complexity and chronological age. Design: Bilingual children were compared with monolingual children matched by age and long-term immigrants (children’s parents) via an Elicited Production task. We elicited the distribution of personal a in simple and Clitic Left Dislocated (CLLD) structures. Data and analysis: Results were entered into r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 56 publications
5
16
1
Order By: Relevance
“…The evidence presented in this paper suggests that school-age child HSs distinguish between human and nonhuman animate, specific DOs in their production of Spanish DOM. This does not mean that groups do not differ in the actual rates of DOM, in line with what previous studies looking at categorical (obligatory) contexts have reported (Cuza et al, 2019;Guijarro-Fuentes & Marinis, 2011;Montrul & Sánchez-Walker, 2013).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The evidence presented in this paper suggests that school-age child HSs distinguish between human and nonhuman animate, specific DOs in their production of Spanish DOM. This does not mean that groups do not differ in the actual rates of DOM, in line with what previous studies looking at categorical (obligatory) contexts have reported (Cuza et al, 2019;Guijarro-Fuentes & Marinis, 2011;Montrul & Sánchez-Walker, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…It has consistently been found that HSs omit DOM with animate direct objects (DOs) more than monolingual speakers and first-generation speakers (e.g., Montrul, 2004;Montrul & Bowles, 2009;Montrul & Sánchez-Walker, 2013;Montrul 2014). Evidence of child HSs has also found similar omission (Cuza et al, 2019;Guijarro-Fuentes & Marinis, 2011;Montrul & Sánchez-Walker, 2013). This suggests that DO animacy (as well as other related features of DOs) may not be such strong constraints on DOM use in HSs, in line with structural simplification accounts.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The picture becomes pellucid when we take into account the heterogeneity found in our child heritage speakers. Like prior research that found no effect of age on bilingual production of Spanish morphosyntax (Cuza et al, 2019), this study found no effect of age on task performance. Nor did we find an effect of English proficiency.…”
Section: Discussionsupporting
confidence: 62%